Енергетична безпека підприємства як інструмент забезпечення його сталого розвитку - Матвійчук, Наталія Миколаївна; Matviichuk, Nataliia M.; Коленда, Наталія Вікторівна; Kolenda, Nataliia V.; Сидорук, Світлана Володимирівна; Sydoruk, Svetlana V. (Мукачівський державний університет, 2019)
Розглянуто наукові підходи до трактування поняття енергетичної безпеки підприємства. Запропоновано власне визначення даної категорії з врахуванням екологічного чинника. Енергетичну безпеку підприємства охарактеризовано як стан технічно надійного, стабільного, якісного, достатнього та екологічно прийнятного забезпечення підприємства всіма видами енергії за економічно вигідною ціною, а також ефективне використання енергетичних ресурсів в процесі господарської діяльності. Обгрунтувано важливість енергетичної безпеки підприємства як інструмента забезпечення його сталого розвитку, що дозволяє розглядати енергетичну безпеку підприємства як стан, за якого енергетичний аспект не є потенційною перешкодою для сталого розвитку підприємства в довгостроковому періоді. Окреслено основні внутрішні та зовнішні загрози енергетичній безпеці підприємства та показники, що використовуються для її оцінки. Запропоновано основні напрями гарантування енергетичної безпеки на рівні підприємства. In the current economic conditions energy security is an important component of an enterprise’s economic security, because the activity of any industrial enterprise is largely determined by the provision of its needs in heat and electric energy. The lack of energy resources and rising prices for it in our country leads to the fact that for the stable functioning of the enterprises they must increase the costs for the supporting their resource base. All of this requires intensive attention to ensuring the energy security of enterprises as one of the priorities of their development and the basis for ensuring energy security of the region and country. The scientific approaches to the interpretation of the concept of energy security of the enterprise are considered. The article proposes an author's definition of this concept taking into account the environmental factor. The energy security of an enterprise considered as a state of technically reliable, stable, qualitative, sufficient and environmentally acceptable provision of the enterprise by all types of energy at cost effective price, as well as efficient use of energy resources in the process of economic activity. The ecological aspect of ensuring the energy security of an enterprise involves the optimal use of non-renewable or limited energy resources, reducing the anthropogenic impact on the environment, development of waste utilization programs with the use of innovative technologies, etc. The importance of energy security of the enterprise as an instrument for ensuring its sustainable development is substantiated. The main internal and external threats to the energy security of the enterprise and the indicators used for its estimation are proposed. The main directions of guarantee energy security at the enterprise level are determined.
Energy security of the company as a tool for ensuring its sustainable development
Keywords: енергетична безпека підприємства; energy security of the enterprise; енергетичні ресурси; energy resources; сталий розвиток підприємства; sustainable development of the enterprise; альтернативні джерела енергії; alternative sources of energy; загрози енергетичній безпеці підприємства; threats to the energy security of the enterprise